Analisis Sebaran Indeks Aksesibilitas Rumah Makan terhadap Objek Wisata di Kawasan Wisata Mandeh - Wedisa, Idma Fitri; Syarief, Azhary (Lembaga Yasin AlSys, 2023)
This study aims to find out the distribution of restaurant facilities and distance to tourist attractions and the accessibility index of restaurant facilities to tourist attractions in Mandeh Tourism Area, Koto XI Tarusan District, Pesisir Selatan Regency. This research uses quantitative descriptive method. The data analysis technique used in this study is a quantitative distance analysis technique using the accessibility index formula. The results showed that 1) The distribution of restaurant facilities and distance to tourist objects obtained as many as 33 distribution of restaurant facilities consisting of 13 traditional and modern restaurants, 8 fast food restaurants and 12 classified as cafes, and there are 30 tourist objects which are divided into 10 natural attractions and 20 marine attractions in the mandeh tourist area. 2) The accessibility index of restaurants to tourist objects has 5 categories, namely a very high accessibility index consisting of 17 restaurant facilities, a high accessibility index consisting of 10 restaurant facilities, a medium accessibility index consisting of 2 restaurant facilities, a low accessibility index consisting of 3 restaurant facilities and a very low accessibility index consisting of 1 restaurant facility. Based on this data, it can be concluded that the accessibility of restaurant facilities to tourist attractions in the Mandeh Tourism Area, Koto XI Tarusan District is included in the very high category or easy to reach by tourists.